Perspektif Kepemimpinan Qur’ani pada Varian Pesantren Terintegrasi - Tamam, Badrut; Isomuddin, Moh.; Istifadah, Istifadah; Muadin, Akhmad; Usriyah, Lailatul (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
Leadership in the organization is necessary. The leadership of a person who has a leadership spirit allows the direction and goals of the organization to be oriented in accordance with the vision and mission. Leadership in the integrated pesantren variant is no exception. The spirit of leadership today in social organizations and educational institutions expects leadership that can provide feedback or a positive impact on the pattern of organizational development, especially in educational institutions. As reflected in the variant of the integrated pesantren, namely Pondok Pesantren Miftahul Ulum Kalisat Jember. This research is to reveal how the perspective of Quranic leadership in the variant of integrated pesantren. The focus of the research uses the analytical knife of Cn Cooley's theory as well as several relevant theories. This type of research uses case studies. Data mining through observation, interviews, and documentation was then analyzed using the steps as presented by Miles and Huberman, namely condensation, display, conclusion, and verification. Based on the analysis, it was found that the Qur'anic leadership perspective in the integrated pesantren variant implements the values ​​in the Qur'an and Hadith. These values ​​are categorized under the principles of Amanah, Khidmah, and Barokah.